A non-dispersible cement-based composite material for underwater repair and a method of making the same
Patent Information
- Application Number
- CN202610993752.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-09-15
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of underwater repair materials technology, and particularly relates to a non-dispersible cement-based composite material for underwater repair and its preparation method. Background Technology
[0002] Underwater engineering structures (such as cross-sea bridges, submarine tunnels, port terminals, and water conservancy dams) are in harsh environments with high salinity, high water pressure, water flow erosion, and chloride ion corrosion for a long time. They are prone to defects such as concrete spalling, crack expansion, and structural deterioration. There is an urgent need to develop efficient, durable, and low-carbon underwater rapid repair technologies.
[0003] Currently, underwater structure repair mainly adopts the traditional method of constructing a cofferdam and then pumping water onto dry land. This method requires the construction of a cofferdam, pumping out the water body, and sealing off the construction area, resulting in significant problems such as long construction period, complex procedures, high operational risks, and high project costs. Furthermore, the construction of the cofferdam and the pumping operation are energy-intensive and generate high carbon emissions, which is incompatible with the requirements of green and low-carbon engineering projects.
[0004] In terms of repair and reinforcement materials, existing underwater cast concrete or mortar generally achieves anti-water dispersion function by adding flocculants, but there are still obvious defects: 1) The slurry is easy to lose, the aggregate is easy to segregate, the density after molding is poor, and the mechanical properties fluctuate greatly; 2) The strength and ductility are significantly deteriorated after underwater molding, the durability is insufficient, and it is difficult to meet the requirements of long-term service; 3) The cement consumption is high and the carbon emissions are large, which does not conform to the development direction of low-carbon engineering.
[0005] Engineering cement-based composites (ECCs) possess excellent properties such as high ductility, multi-crack propagation, and micro-crack self-control, and have been widely used in onshore structure repair. However, when conventional ECCs are directly applied to underwater environments, they face the following key technical bottlenecks: 1) Lack of underwater anti-dispersion design, resulting in severe slurry loss during underwater casting and difficulty in forming; 2) Underwater disturbance leads to coarsening of pore structure, increased porosity, and uneven hydration, resulting in a significant decrease in mechanical properties; 3) Lack of specialized mix proportions and preparation processes adapted to underwater environments, making it difficult to synergistically match flowability, anti-dispersion properties, and mechanical properties; 4) Difficulty in achieving both high ductility and underwater non-dispersion properties, making direct casting without cofferdams impossible; 5) Lack of systematic understanding of underwater mechanical degradation mechanisms, making performance control and engineering design difficult.
[0006] In summary, existing underwater repair technologies and materials cannot simultaneously meet the comprehensive requirements of "water resistance, self-leveling, high ductility, stable strength, low carbon and low cost, and cofferdam-free construction," making it difficult to meet the actual needs of modern marine engineering and water conservancy projects for rapid, safe, green, and long-term repair of underwater structures. Summary of the Invention
[0007] To address the problems of high construction costs, high carbon emissions, and long construction periods associated with existing underwater repair materials and construction technologies, as well as the issues of easy dispersion, poor density, significant mechanical degradation, insufficient ductility, and large cement consumption in underwater casting materials, this invention proposes a non-dispersible cement-based composite material for underwater repair and its preparation method. This composite material can be directly cast underwater without cofferdams and features resistance to water dispersion, high ductility, high strength retention, and green, low-carbon characteristics. This invention also provides a standardized preparation and underwater molding method to achieve efficient, durable, and low-carbon repair of underwater structures in marine and hydraulic engineering projects.
[0008] To achieve the above objectives, the present invention provides the following technical solution: One objective is to develop a non-dispersible cementitious composite material for underwater remediation, comprising the following components per cubic meter: 440–470 kg of cement, 840–900 kg of fly ash, 38–44 kg of silica fume, 330–360 kg of quartz sand, 390–430 kg of mixing water, 8–30 kg of flocculant, 2.2–2.6 kg of water-reducing agent, 1.2–1.6 kg of early-strength agent, 100–120 kg of polyurethane prepolymer, 8–10 kg of nano-silica, and fiber; wherein the water-cement ratio is 0.29–0.30; and the fly ash accounts for ≥60% of the mass of the cementitious material.
[0009] Furthermore, the non-dispersible cement-based composite material comprises the following components per cubic meter: 455.4 kg of cement, 869.3 kg of fly ash, 41.4 kg of silica fume, 344.9 kg of quartz sand, 413.9 kg of mixing water, 8-12 kg of anionic polyacrylamide flocculant, 2.4 kg of water-reducing agent, 1.4 kg of early-strength agent, 100 kg of polyurethane prepolymer, 10 kg of nano-silica, and 18.5 kg of polyethylene fiber; the water-cement ratio is 0.30.
[0010] Furthermore, the non-dispersible cement-based composite material comprises the following components per cubic meter: 455.4 kg of cement, 869.3 kg of fly ash, 41.4 kg of silica fume, 344.9 kg of quartz sand, 413.9 kg of mixing water, 27.3 kg of polyaluminum chloride flocculant, 2.6 kg of water-reducing agent, 120 kg of polyurethane prepolymer, 9 kg of nano-silica, and 1.4 kg of early strength agent; the volume content of polyvinyl alcohol fiber is 2%; and the water-cement ratio is 0.30.
[0011] Furthermore, the non-dispersible cement-based composite material comprises the following components per cubic meter: 455.4 kg of cement, 869.3 kg of fly ash, 41.4 kg of silica fume, 344.9 kg of quartz sand, 396.2 kg of mixing water, 27.3 kg of polyaluminum chloride flocculant, 2.4–2.6 kg of water-reducing agent, 1.4 kg of early-strength agent, 110 kg of polyurethane prepolymer, 8 kg of nano-silica, and 18.5 kg of polyethylene fiber; the water-cement ratio is 0.29.
[0012] Furthermore, the water-reducing agent is a polycarboxylate superplasticizer.
[0013] Furthermore, the early strength agent is calcium formate.
[0014] Second objective: A method for preparing a non-dispersible cementitious composite material for underwater remediation, comprising the following steps: (1) The fibers are pretreated to disperse; (2) Mix cement, fly ash, silica fume, quartz sand, flocculant, early strength agent, nano silica and pretreated fiber and stir evenly to obtain dry mix; (3) Add 70% of the mixing water and water-reducing agent to the dry mixture and stir well, then add the polyurethane prepolymer and the remaining 30% of the mixing water to obtain the slurry; (4) The slurry is sealed and poured underwater; (5) After the cast sample has been cured for 24 hours, the mold is removed and then placed in a saturated Ca(OH)2 curing box for 28 days.
[0015] The mechanism of action of the composite material of the present invention is as follows: First, the polyurethane prepolymer can synergistically improve the overall cohesiveness, toughness and bonding strength of the new and old interfaces of the slurry with cement slurry, improve the impermeability of the material, reduce the intrusion of water and corrosive media, and directly reduce the dispersion and loss of slurry under dynamic water conditions. Meanwhile, nano-silica can accelerate cement hydration through pozzolanic reaction and heterogeneous nucleation effect, refine the internal pore structure, further reduce the proportion of harmful pores, block the erosion path, and improve the compressive strength, slurry density and viscosity of the material. Together with the polyurethane prepolymer, it can simultaneously enhance the anti-dispersion effect from two dimensions: "macroscopic slurry cohesion" and "microscopic particle filling". At the same time, it can jointly optimize the mechanical properties in terms of toughness, bonding strength and durability. The flocculant (polyaluminum chloride) hydrolyzes to form Al(OH)3 colloid, which encapsulates particles through adsorption bridging and charge neutralization, forming a stable anti-dispersion film to ensure that the material is not lost during underwater casting. The flocculant (anionic polyacrylamide) dissolves in water and ionizes and unfolds its long polymer chains, which encapsulate the gel powder particles through electrostatic adsorption, molecular chain bridging and hydrogen bonding, forming a highly viscous polymer anti-dispersion protective film that resists water dilution and erosion, ensuring that the material is not lost or segregated during underwater casting. Secondly, regarding high ductility, the fibers form a three-dimensional network within the matrix, providing bridging stress when cracks occur, enabling steady-state propagation of multiple microcracks and exhibiting strain hardening characteristics. Thirdly, regarding low degradation, by controlling the cementitious ratio (fly ash + microsilica) and cement dosage, the degree of hydration, porosity, and interfacial bonding are optimally balanced, thereby minimizing the increase in porosity caused by the underwater environment. Fourthly, regarding low carbon footprint, the fly ash content is ≥60%, significantly replacing cement and reducing limestone calcination and corresponding CO2 emissions. Finally, regarding the elimination of cofferdams, relying on the material's inherent anti-dispersion properties and specialized underwater casting technology, construction can proceed directly without waterstopping, pumping, or cofferdam erection. These five mechanisms work synergistically to achieve the high efficiency, durability, and green low-carbon goals of this invention in underwater remediation engineering.
[0016] Third objective: Application of a non-dispersible cement-based composite material for underwater repair in underwater repair projects without cofferdams.
[0017] Furthermore, the underwater cofferdam-free repair project includes the underwater structural repair of cross-sea bridges, submarine tunnels, port terminals, water conservancy dams, and offshore wind power foundations.
[0018] Compared with the prior art, the present invention has the following advantages and technical effects: This invention addresses the problems of material dispersion and loss by employing a flocculation system combined with a sealed underwater casting process to ensure that the slurry does not disperse or leak underwater. Regarding significant mechanical degradation, it effectively suppresses the decline in underwater mechanical properties by optimizing the cementitious ratio, introducing fiber toughening, and forming a fine porous structure. Addressing the issues of requiring cofferdams and high construction costs, this material can be directly cast underwater, eliminating the need for cofferdam construction and pumping. For high carbon emissions, the fly ash content is ≥60%, significantly replacing cement and substantially reducing carbon emissions and energy consumption. Furthermore, addressing the issues of insufficient ductility and easy cracking in traditional materials, the fibers still enable multi-microcrack propagation and strain hardening underwater, endowing the material with excellent high ductility. The synergistic effect of these technologies comprehensively solves the core defects of existing underwater repair materials and construction techniques. Detailed Implementation
[0019] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0020] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0021] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0022] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0023] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0024] This invention addresses the technical challenges of existing underwater repair materials, such as easy dispersion, significant mechanical degradation, the need for cofferdams during construction, and high carbon emissions. It provides a non-dispersible, high-ductility cementitious composite material for underwater repair, and discloses its precise proportioning, preparation steps, underwater-specific molding process, and mechanism of action. Through the synergistic effect of five key technologies—a high-fly ash low-carbon cementitious system, flocculation and anti-dispersion components, a fiber-reinforced network, a step-by-step mixing process, and an underwater sealing casting process—the material achieves comprehensive performance characteristics including non-dispersion underwater, self-leveling, high ductility, stable strength, no need for cofferdams, and low carbon and low cost, allowing those skilled in the art to repeat the process according to the instructions. The composite material comprises the following components: (1) Cementitious materials: composed of P·O52.5 grade ordinary Portland cement, grade I fly ash, and microsilica; fly ash accounts for ≥60% of the mass of cementitious materials, achieving high-content solid waste with low carbonization. Cement can provide early strength and hydration matrix, providing basic mechanical support for the system; fly ash can play a role in improving fluidity through microbead effect, and secondary hydration in the later stage refines the pore structure and reduces carbon emissions; microsilica can fill the pores of the matrix, improving density, strength and impermeability.
[0025] (2) Aggregate: 70-120 mesh quartz sand, which is uniformly dispersed in the matrix as a skeleton and does not produce segregation.
[0026] (3) Functional components: 1) Flocculant: Anionic polyacrylamide and polyaluminum chloride are uniformly dispersed in the slurry, encapsulating the gel particles to form an anti-dispersion film; the flocculant can encapsulate the particles through adsorption bridging and charge neutralization to achieve underwater anti-dispersion; 2) Polycarboxylate superplasticizer: It is uniformly adsorbed on the surface of cementitious particles, reducing the water-cement ratio and improving fluidity; it can achieve crack bridging and multi-crack control, thereby achieving high ductility and strain hardening. 3) Early strength agent: calcium formate, which is evenly distributed and promotes early hydration, shortening the molding cycle.
[0027] (4) Reinforcing components: 1) Polyethylene fiber (PE) or polyvinyl alcohol fiber (PVA, length 12-18mm) is three-dimensionally disordered and uniformly distributed inside the matrix to form fiber-matrix interface bonding and provide crack bridging effect.
[0028] 2) Polyurethane prepolymer can work synergistically with cement slurry to improve the overall cohesiveness, toughness and bonding strength of the new and old interfaces of the slurry, improve the impermeability of the material, reduce the intrusion of water and corrosive media, and directly reduce the dispersion and loss of slurry under dynamic water conditions. 3) Nano-silica can accelerate cement hydration through volcanic ash reaction and heterogeneous nucleation effect, refine the internal pore structure, further reduce the proportion of harmful pores, block erosion pathways, and improve the compressive strength, slurry density and viscosity of the material.
[0029] (5) Mixing water: uniformly fills the gaps between particles, participates in the hydration reaction, and controls the rheological properties of the slurry.
[0030] This invention provides a non-dispersible cementitious composite material for underwater remediation, comprising the following components per cubic meter: 440-470 kg of cement, 840-900 kg of fly ash, 38-44 kg of silica fume, 330-360 kg of quartz sand, 390-430 kg of mixing water, 8-30 kg of flocculant, 2.2-2.6 kg of water-reducing agent, 1.2-1.6 kg of early-strength agent, 100-120 kg of polyurethane prepolymer, 8-10 kg of nano-silica, and fiber; wherein the water-cement ratio is 0.29-0.30; and the fly ash accounts for ≥60% of the mass of the cementitious material.
[0031] In the following optional embodiments of the present invention, different formulations can be selected according to the application environment: Option 1: Suitable for low-temperature underwater environments. Per cubic meter: 455.4 kg cement, 869.3 kg fly ash, 41.4 kg silica fume, 344.9 kg quartz sand, 413.9 kg mixing water, 8-12 kg anionic polyacrylamide flocculant, 2.4 kg water-reducing agent, 1.4 kg early-strength agent, 100 kg polyurethane prepolymer, 10 kg nano-silica, and 18.5 kg polyethylene fiber; water-cement ratio is 0.30.
[0032] Option 2: Suitable for ordinary water conservancy projects that are more sensitive to costs. Per cubic meter: 455.4 kg cement, 869.3 kg fly ash, 41.4 kg silica fume, 344.9 kg quartz sand, 413.9 kg mixing water, 27.3 kg polyaluminum chloride flocculant, 2.6 kg water-reducing agent, 120 kg polyurethane prepolymer, 9 kg nano-silica, and 1.4 kg early-strength agent; the volumetric content of polyvinyl alcohol fiber is 2%; the water-cement ratio is 0.30.
[0033] Option 3: Suitable for repair projects with higher underwater strength requirements. Per cubic meter: 455.4 kg cement, 869.3 kg fly ash, 41.4 kg silica fume, 344.9 kg quartz sand, 396.2 kg mixing water, 27.3 kg polyaluminum chloride flocculant, 2.4–2.6 kg water-reducing agent, 1.4 kg early-strength agent, 110 kg polyurethane prepolymer, 8 kg nano-silica, and 18.5 kg polyethylene fiber; water-cement ratio is 0.29.
[0034] The internal structure and connection relationship of the composite material of the present invention are as follows: the matrix is a continuous and dense cement-based gel phase, which is generated by secondary hydration of fly ash and microsilica to form hydrated calcium silicate (alumina) gel (C-(A)-SH gel); quartz sand is uniformly embedded in the matrix as aggregate, and the interfacial transition zone (ITZ) is dense; PE fibers penetrate the interior of the matrix and form a chemical bond and friction bond composite interface with the matrix; the polyurethane prepolymer and cement slurry synergistically improve the overall cohesiveness, toughness and bonding strength of the old and new interfaces of the slurry, improve the impermeability of the material, reduce the intrusion of water and corrosive media, and directly reduce the dispersion and loss of slurry under dynamic water conditions; nano silica can accelerate cement hydration through pozzolanic reaction and heterogeneous nucleation effect, refine the internal pore structure, further reduce the proportion of harmful pores, block the erosion path, and improve the compressive strength, slurry density and viscosity of the material, and simultaneously enhance the anti-dispersion effect with polyurethane prepolymer from two dimensions: "macroscopic slurry cohesion" and "microscopic particle filling". The flocculant encapsulates the particles in a membrane structure, forming an overall anti-dispersion system; the internal pores are mainly gel pores and capillaries, without interconnected macropores, thus ensuring underwater strength stability.
[0035] The preparation method of the above-mentioned non-dispersible cement-based composite material for underwater remediation includes the following steps: (1) The fiber is dispersed and pretreated by a blower; after the fiber is forcibly dispersed by the blower, the clumping can be eliminated, thereby ensuring that the fiber is evenly distributed in three dimensions in the slurry and avoiding local aggregation to form weak areas; (2) Add cement, fly ash, microsilica powder, quartz sand, flocculant, early strength agent, nano silica and pretreated fiber into a mixer and stir at low speed for 60 seconds until uniform to obtain dry mix; wet the inner wall of the mixer with a damp cloth, mix the raw materials according to the proportion and stir at low speed to pre-disperse the solid particles and avoid local agglomeration of flocculant. (3) Add 70% of the mixing water and water-reducing agent to the dry mix, stir at low speed for 1 minute, stir at high speed for 2 minutes, then add the polyurethane prepolymer and the remaining 30% of the mixing water, and stir until the slurry is uniform and the fibers are well dispersed to obtain the slurry; the mixing method of adding the mixing water in batches can first form a low water-binder ratio and high dispersion system, and then adjust the fluidity. This method takes into account both anti-dispersion and workability. (4) Immerse the mold completely in water, with the water level 150mm above the top surface of the mold; use a bottom-sealed grouting pipe to fill the mold, and release the seal after the grouting pipe touches the bottom, lift it slowly and uniformly and continuously pour the grout; after the specimen is taken out, let it stand in the air for 10 minutes, tap the four corners of the mold to drain the water, and level the surface; this underwater casting molding step can avoid water disturbance, prevent grout loss, and ensure that the molding is dense and uniform. (5) Remove the mold after 24 hours of standard curing and place it in a saturated Ca(OH)2 curing box for 28 days.
[0036] The aforementioned non-dispersible cement-based composite materials for underwater repair can be applied to underwater cofferdam-less repair projects. These projects include the underwater structural repair of cross-sea bridges, submarine tunnels, port terminals, hydraulic dams, and offshore wind power foundations.
[0037] The composite material provided by this invention has the following significant advantages: I. Technical Effects: Excellent underwater anti-dispersion performance; low suspended solids content during underwater casting; pH meets standards (≤12), fully satisfying the requirements for underwater non-dispersible materials, avoiding slurry loss, aggregate segregation, and loose molding. Excellent fluidity and workability; mortar flowability meets standards (≥180mm); good self-leveling properties; no vibration required; easily fills complex underwater structures. Minimal degradation of underwater mechanical properties; high strength retention: under optimized mix design, significant strain hardening and multi-microcrack characteristics are maintained both underwater and on land. Outstanding high ductility and crack control; generates numerous fine and uniform microcracks during tensile testing, with no penetrating main cracks, significantly improving durability. Dense pore structure; stable microstructure; small increase in porosity after underwater casting; no interconnected macropores; high matrix density; superior impermeability and erosion resistance compared to conventional underwater concrete and ordinary ECC.
[0038] II. Economic Benefits: The ECC repair scheme eliminates the need for cofferdams and dewatering, resulting in a lower total cost per unit project compared to traditional cofferdam construction. The high proportion of industrial solid waste (fly ash ≥60%) largely replaces cement, reducing raw material costs while generating added value through solid waste disposal. The simplified construction process shortens the construction period by over 50%, allowing for construction by a single person and with small equipment, significantly reducing labor costs.
[0039] III. Environmental and Social Impacts: Compared to traditional cofferdam repair methods, the ECC (Energy Conversion Control) emissions over the entire life cycle are lower, energy consumption is reduced, and the use of cofferdam steel, electricity for pumping, and fuel for machinery is eliminated. Construction safety risks are significantly reduced, eliminating the need for high-altitude operations on water, deep-water cofferdams, and prolonged closure of waterways, resulting in minimal disturbance to the aquatic environment. Solid waste is utilized for resource recovery, with a large amount of fly ash being disposed of, reducing land occupation and environmental pollution, and promoting low-carbon and sustainable development of marine engineering.
[0040] IV. Engineering Applications: This technology truly enables rapid underwater repair without cofferdams or drainage, suitable for scenarios where traditional methods are difficult to implement, such as tidal zones, splash zones, and deep-water structures. It has a wide range of applications, suitable for repairing various underwater structures, including cross-sea bridges, subsea tunnels, port terminals, hydraulic dams, and offshore wind power foundations. The process is simple, highly repeatable, and uses commercially available conventional materials. Preparation and casting require no specialized equipment, facilitating engineering-scale promotion.
[0041] All raw materials used in this invention were purchased from the market.
[0042] The technical solution of the present invention will be further illustrated by the following embodiments.
[0043] In the following examples, the high-speed stirring speed is 1000 rpm and the low-speed stirring speed is 200 rpm.
[0044] The fibers are pretreated with a blower before use to reduce agglomerates.
[0045] Example 1 A non-dispersible cement-based composite material for underwater remediation is prepared as follows: 1) Weigh the following per cubic meter: cement 455.4 kg, fly ash 869.3 kg, silica fume 41.4 kg, quartz sand 344.9 kg, mixing water 413.9 kg, anionic polyacrylamide flocculant 10 kg, polycarboxylate superplasticizer 2.4 kg, calcium formate early strength agent 1.4 kg, polyurethane prepolymer 100 kg, nano silica 10 kg, and polyethylene fiber 18.5 kg; water-cement ratio is 0.30. 2) The fibers are pre-treated by forced dispersion using a fan to prevent clumping; 3) Add cement, fly ash, silica fume, quartz sand, flocculant, early strength agent, nano silica and pretreated fiber into the mixer and mix at low speed for 60 seconds until uniform; 4) Add 70% of the mixing water and all the water-reducing agent to the mixer, mix at low speed for 1 minute, then mix at high speed for 2 minutes; then add the polyurethane prepolymer and the remaining 30% of the mixing water, and continue mixing until the slurry is uniform and the fibers are completely dispersed. 5) Immerse the mold completely in water, with the water level 150mm above the top surface of the mold; use a bottom-sealed grouting pipe to fill the mold, and after the bottom is unsealed, lift it slowly and continuously pour the grout; after the specimen is formed, let it stand in the air for 10 minutes, gently tap the four corners of the mold to drain the water and level the surface. 6) Remove the mold after 24 hours of standard curing, and then place it in a saturated Ca(OH)2 curing chamber for 28 days.
[0046] Performance testing 1. Water dispersibility test: The water dispersibility of the prepared composite material is tested according to DL / T 5117-2021 "Test Procedure for Underwater Non-dispersible Concrete". If the suspended solids content is ≤250mg / L and the pH value is ≤12, it is determined to meet the requirements of underwater non-dispersible material.
[0047] Tests showed that the suspended solids content of the composite material prepared in Example 1 was 202 mg / L and the pH value was 10.59, which fully met the standard requirements.
[0048] 2. Flowability test: The flowability of the prepared composite material was tested according to GB / T 2419-2005 "Method for Determination of Flowability of Cement Mortar".
[0049] Tests showed that the mortar spread of the composite material prepared in Example 1 was 195 mm (≥180 mm), thus the self-leveling performance of the composite material was determined to be excellent.
[0050] 3. Compressive strength test: The compressive strength of the prepared composite material was tested according to JC / T 2461-2018 "Test method for mechanical properties of high ductility fiber reinforced cementitious composite materials".
[0051] The composite material prepared in Example 1 was tested and found to have a land compressive strength of 7.95 MPa and an underwater compressive strength of 6.36 MPa, with a strength ratio of 80.38%.
[0052] 4. Uniaxial tensile test: The prepared composite material was subjected to uniaxial tensile test according to JC / T 2461-2018.
[0053] The underwater ultimate tensile strength of the composite material prepared in Example 1 was tested to be 5.58 MPa and the underwater ultimate tensile strain was 6.92%. Therefore, it was determined that the underwater mechanical degradation of the composite material was small and that it could maintain strain hardening and multi-microcrack characteristics.
[0054] In summary, the composite material prepared in Example 1 is non-dispersible, non-bleeding, and has good self-leveling properties underwater. Its underwater / land compressive strength ratio is ≥80%, and its underwater ultimate tensile strain is ≥6.0%. It can be directly used for rapid repair of underwater structures without cofferdams.
[0055] Example 2 A non-dispersible cement-based composite material for underwater remediation is prepared as follows: Same as Example 1, except that the formula is as follows: 455.4 kg of cement, 869.3 kg of fly ash, 41.4 kg of silica fume, 344.9 kg of quartz sand, 413.9 kg of mixing water, 27.3 kg of polyaluminum chloride flocculant, 2.6 kg of polycarboxylate superplasticizer, 120 kg of polyurethane prepolymer, 9 kg of nano silica, and 1.4 kg of calcium formate early strength agent; the volume content of polyvinyl alcohol fiber is 2%; and the water-binder ratio is 0.30.
[0056] Example 3 A non-dispersible cement-based composite material for underwater remediation is prepared using the same method as in Example 1, except that the formula is as follows: 455.4 kg of cement, 869.3 kg of fly ash, 41.4 kg of silica fume, 344.9 kg of quartz sand, 396.2 kg of mixing water, 27.3 kg of polyaluminum chloride flocculant, 2.5 kg of polycarboxylate superplasticizer, 1.4 kg of calcium formate early strength agent, 110 kg of polyurethane prepolymer, 8 kg of nano-silica, and 18.5 kg of polyethylene fiber; the water-cement ratio is 0.29.
[0057] Comparative Example 1 A non-dispersible cement-based composite material for underwater remediation is prepared in the same way as in Example 1, except that the formula is as follows: 500 kg of cement, 800 kg of fly ash, 41.4 kg of silica fume, 344.9 kg of quartz sand, 413.9 kg of mixing water, 10 kg of anionic polyacrylamide flocculant, 2.4 kg of polycarboxylate superplasticizer, 1.4 kg of calcium formate early strength agent, and 18.5 kg of polyethylene fiber.
[0058] Comparative Example 2 A non-dispersible cement-based composite material for underwater remediation is prepared using the same method as in Example 1, except that the addition of polyurethane prepolymer is omitted.
[0059] Comparative Example 3 A non-dispersible cement-based composite material for underwater remediation is prepared using the same method as in Example 1, except that the addition of nano-silica is omitted.
[0060] The performance of the cement-based composite materials prepared in each example and comparative example was tested according to the method in Example 1, and the results are shown in Table 1.
[0061] Table 1. Statistical table of performance test results for cement-based composite materials As shown in Table 1, the cement-based composite materials prepared in Examples 1-3 exhibit good underwater non-dispersion, no loss, and self-leveling properties, with an underwater / land compressive strength ratio ≥80% and an underwater ultimate tensile strain ≥6.0%, making them suitable for direct use in rapid underwater structure repair without cofferdams. In Comparative Example 1, the fly ash content in the cementitious material is less than 60%. The performance of Examples 1-3 shows minimal differences compared to Comparative Example 1. Examples 1-3 increased the fly ash content, resulting in a significant cost reduction compared to Examples 1-3 without significantly affecting performance. Comparative Examples 2 and 3 omitted polyurethane prepolymer and nano-silica, respectively, from Example 1, leading to a significant decrease in various properties, especially mechanical properties. This suggests that polyurethane prepolymer and nano-silica have a synergistic effect in improving the water dispersibility and other mechanical properties of the cement-based composite materials.
[0062] The above are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A non-dispersible cementitious composite material for underwater repair, characterized in that, Per cubic meter, it includes the following components: 440-470 kg of cement, 840-900 kg of fly ash, 38-44 kg of silica fume, 330-360 kg of quartz sand, 390-430 kg of mixing water, 8-30 kg of flocculant, 2.2-2.6 kg of water-reducing agent, 1.2-1.6 kg of early-strength agent, 100-120 kg of polyurethane prepolymer, 8-10 kg of nano-silica, and fiber; The water-cement ratio is 0.29–0.30; the fly ash accounts for ≥60% of the mass of the cementitious material.
2. The non-dispersible cementitious composite material for underwater repair according to claim 1, characterized in that, The non-dispersible cement-based composite material comprises the following components per cubic meter: 455.4 kg of cement, 869.3 kg of fly ash, 41.4 kg of silica fume, 344.9 kg of quartz sand, 413.9 kg of mixing water, 8-12 kg of anionic polyacrylamide flocculant, 2.4 kg of water-reducing agent, 1.4 kg of early-strength agent, 100 kg of polyurethane prepolymer, 10 kg of nano-silica, and 18.5 kg of polyethylene fiber; the water-cement ratio is 0.
30.
3. The non-dispersible cementitious composite material for underwater repair according to claim 1, wherein, The non-dispersible cement-based composite material comprises the following components per cubic meter: 455.4 kg of cement, 869.3 kg of fly ash, 41.4 kg of silica fume, 344.9 kg of quartz sand, 413.9 kg of mixing water, 27.3 kg of polyaluminum chloride flocculant, 2.6 kg of water-reducing agent, 120 kg of polyurethane prepolymer, 9 kg of nano-silica, and 1.4 kg of early strength agent; the volume content of polyvinyl alcohol fiber is 2%; and the water-cement ratio is 0.
30.
4. The non-dispersible cementitious composite material for underwater repair of claim 1, wherein, The non-dispersible cement-based composite material comprises the following components per cubic meter: 455.4 kg of cement, 869.3 kg of fly ash, 41.4 kg of silica fume, 344.9 kg of quartz sand, 396.2 kg of mixing water, 27.3 kg of polyaluminum chloride flocculant, 2.4–2.6 kg of water-reducing agent, 1.4 kg of early-strength agent, 110 kg of polyurethane prepolymer, 8 kg of nano-silica, and 18.5 kg of polyethylene fiber; the water-cement ratio is 0.
29.
5. The non-dispersible cementitious composite material for underwater repair according to any one of claims 1 to 4, characterized in that, The water-reducing agent is a polycarboxylate superplasticizer.
6. The non-dispersible cementitious composite material for underwater remediation according to any one of claims 1 to 4, characterized in that, The early strength agent is calcium formate.
7. A method for preparing a non-dispersible cementitious composite material for underwater remediation as described in any one of claims 1 to 6, characterized in that, Includes the following steps: (1) The fibers are pretreated to disperse; (2) Mix cement, fly ash, silica fume, quartz sand, flocculant, early strength agent, nano silica and pretreated fiber and stir evenly to obtain dry mix; (3) Add 70% of the mixing water and water-reducing agent to the dry mixture and stir well, then add the polyurethane prepolymer and the remaining 30% of the mixing water to obtain the slurry; (4) The slurry is sealed and poured underwater; (5) After the cast sample has been cured for 24 hours, the mold is removed and then placed in a saturated Ca(OH)2 curing box for 28 days.
8. The application of a non-dispersible cement-based composite material for underwater repair as described in any one of claims 1 to 6 in underwater repair projects without cofferdams.